Fundusz Rezerwy Demograficznej – analiza działalności oraz konsekwencje przedterminowego wykorzystania aktywów - Rutecka, Joanna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2013)
Demographic Reserve Fund (FRD) has been created in Poland in 2002 to offer additional source of financing for old-age pension system in case it faces significant deficit resulting from demographic reasons. This buffer fund aims mainly at balancing the incomes and expenditures of pension system in times when baby boomers will be offered old-age pension benefits. The main sources of its financing were defined as pension contributions and revenues from privatization of state owned companies. But after several years of its activity it has turned out that the operations of the fund came in contradiction with its main goals, mainly due to early usage of its assets. The article presents main characteristics of Polish Demographic Reserve Fund, basic principles of its functioning, portfolio structure and rates of return. Moreover, it tries to give some opinion in hot debate about the purposes and effects of accumulating assets in pension reserve funds in times of budget shortages.